PENGARUH TINGKAT PEMBERIAN KONSENTRAT TERHADAP DAYA CERNA BAHAN KERING DAN PROTEIN KASAR RANSUM PADA SAPI BALI JANTAN YANG MENDAPATKAN RUMPUT RAJA (Pennisetum purpurephoides) Ad-libitum - Muh. Yasaf A. Koddang (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
This experiment was aimed to examine the addition of concentrate on dry matter and crude protein digestibility of Bali steers given King grass (Pennisetum purpurephoides). The experiment was conducted in village Oloboju sub district of Sigi Biromaru district of Donggala. Five Bali steers used in the experiment. Their weight ranged from 125 kg to 182 kg. The animals placed on permanent pen with concrete floor. The pen was divided into five plotseach for animal placement and treatment. The experiment design used was a latin square 5 x 5. There was five period, each period consisted of 2 step namely preliminary and data collection period which was 7 day each. The treatment employed 0.0% ; 0.5% ; 1.0% ; 1.5% ; 2.0% of animal weight of concentrate. The basal diet was King grass ad-libitum. The result of variance analysis showed that level of addition concentrate to King grass significantly affected (P<0.01) digestibility of dry matter and crude protein of feed of Bali steers. The higher concentrate level the higher dry matter digestibility of feed. The crude protein digestibility responded quadratically to level of concentrate addition.